Transplantation of induced pluripotent stem cells-derived cardiomyocytes combined with modified Taohong Siwu decoction improved heart repair after myocardial infarction - Zhi-rong Luo; Wan-ting Meng; Han Li; Yu Wang; Ya-chao Wang; Yue Zhao; Ping-ping Lu; Yuan Yuan; Wei Huang; Hai-dong Guo (Heliyon, 2024)
Objective: This study aimed to study whether modified Taohong Siwu decoction (MTHSWD) combined with human induced pluripotent stem cells-derived cardiomyocytes (iPS-CMs) transplantation can promote cardiac function in myocardial infarction (MI) nude mouse model and explore its possible mechanism. Methods: The MI mouse model was established by the ligation of left anterior descending coronary artery. After 4 weeks of gavage of MTHSWD combined with iPS-CMs transplantation, the changes in heart function of mice were examined by echocardiography. The histological changes were observed by Masson's trichrome staining. The survival and differentiation of transplanted cells were detected by double immunofluorescence staining of human nuclear antigen (HNA) and cardiac troponin T (cTnT). The number of c-kit-positive cells in the infarct area were evaluated by immunofluorescent staining. The levels of stromal cell-derived factor 1 (SDF-1), stem cell factor (SCF), vascular endothelial growth factor (VEGF) and basic fibroblast growth factor in infarcted myocardium tissues were detected by ELISA. Results: MTHSWD combined with iPS-CMs transplantation can improve the heart function of MI mice, reduce the infarct size and collagen deposition in infarct area. By immunofluorescence double-label detection of HNA and cTnT, it was found that MTHSWD combined with iPS-CMs transplantation can improve the survival and maturation of iPS-CMs. In addition, MTHSWD combined with iPS-CMs transplantation can activate more endogenous c-kit positive cardiac mesenchymal cells, and significantly increase the content of SDF-1, SCF and VEGF in myocardial tissues. Conclusions: The combination of MTHSWD with iPS-CMs transplantation promoted cardiac function of nude mice with MI by improving the survival and maturation of iPS-CMs in the infarct area, activating the endogenous c-kit positive cardiac mesenchymal cells, and increasing paracrine.